Pengungkapan AkuntansiPertanggungjawaban Sosial(CorporateSocial Responsibility Disclosure) sebagaiPengungkapan Sukarela Kebutuhan InformasiStakeholderpada Official Website Perusahaan (Studi Pada Pt. Indosat Tbk) - Irmadariyani, Ririn (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2010)
The purpose of this research is to see whether the company has taken advantage of the official website to disclose CSR programs conducted. Research conducted at the official site of PT. Indosat Tbk. http://www.indosat.com address in this research focus includes the corporate governance (Government Organization), environmental accounting as a social responsibility. There are two categories that will be used to investigate the reported disclosure of CSR. The first category is the disclosure of information relating to internal stakeholders and the second related information external stakeholders. To measure the quantity of information presented is used as an indicator of Publicity Index. This index indicates the amount of information disclosed by the company as much as 86 questions that there are 2 categories of management and shareholders of the category of internal stakeholders and information to customers, suppliers, environment, society and the distributors of the categories of external stakeholders. The results showed that the index Publicity PT. Indosat Tbk. has revealed 81 of the 86 information relevant to the CSR to the public through the official website. Index derived from the disclosure of information relating to the stakeholders including the reporting of information for 31 categories of internal stakeholders consist of 14 reported that the disclosure of information relating to employee / labor, and 17 reported that the disclosure of information relating to the shareholders and board of directors, as well as stakeholder category for external reporting as many as 50 information that consists of 14 reporting of customer information, supplier information reporting 8 (suppliers), 10 reporting of environmental policies, 12 reported the information society, and 6 reporting the information to distributors. Key Words: Corporate Social Responsibility index publicity official website